Localization of the GoLoco motif carrier regulator of G-protein signalling 12 and 14 proteins in monkey and rat brain - López-Aranda, Manuel Francisco; Acevedo, Maria J.; Carballo, Francisco J.; Gutiérrez-Pérez, Antonia; Khan, Zafaruddin (WILEY, 2006)
Regulator of G-protein signalling (RGS)12 and -14 proteins possess the RGS domain, Ras-binding domains and the GoLoco motif. Emerging evidence suggests that these proteins are involved in several cellular functions in addition to stimulation of GTPase activity of G-protein alpha subunits. However, our understanding of the role of the two proteins in brain function remains marginal. Here, we have studied the expression pattern of RGS12 and RGS14 proteins in brain at regional, cellular and subcellular levels. Both proteins were expressed throughout the brain regions, including cortex, hippocampus, striatum, thalamus and substantia nigra. The most intense immunostaining for RGS12 was seen in cortex and that of RGS14 was found in striatum. In cortex, RGS12 and RGS14 proteins were associated with pyramidal and nonpyramidal cell types. Apical dendrites of pyramidal cells were also labelled. RGS12 was found in both nuclear and cytoplasmic compartments. In contrast to RGS12 protein, RGS14 was localized in astrocytes in addition to neurons. Pyramidal cells in the CA1 area showed labelling for both RGS proteins. The presence of RGS12 was predominantly nuclear in the striatum of rat brain; however, the labelling of this protein was non-nuclear in adult monkey brain. To our surprise, in 1-month-old monkey brain the immunostaining pattern of the same protein was changed to nuclear. Non-nuclear staining for RGS12 was also evident in thalamus of adult monkey brain; however, in 1-month-old monkey brain, it was seen into two different populations, one with nuclear and the other with cytoplasmic staining. Both RGS12 and RGS14 were exclusively localized at postsynaptic sites of excitatory synapses. Our results demonstrate a highly dynamic expression pattern of RGS12 and RGS14 proteins in the central nervous system, and support the view that these proteins may participate not only in G-protein receptor signalling pathways but also in other cellular activities.
Keywords: Inmunocitoquímica; Light and electron microscopy; Receptor signalling; Immunocytochemistry; Protein expression; Brain distribution